On the Blended Solutions of Polynomial-Like Iterative Equation with Multivalued Functions - Jinghua Liu; Hongjuan Duan; Zhiheng Yu (Discrete Dynamics in Nature and Society)
The blended solutions are more general than the unblended solutions for polynomial-like iterative equation with multivalued functions. In this paper we study the blended solutions of polynomial-like iterative equation with multivalued functions.